WORKING WITH CHALLENGES OF HISTORIC SCALE DURING INTER-PARADIGM TRANSITION - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
The cataclysms of the beginning of the 3rd millennium are a feature of parting with the social structure and world order, which were becoming a thing of the past. The maturation of a new social paradigm breaks the old forms. Uncertainty, mutual penetration of fragments of different structures, mobility of boundaries increases, the ratio of norms and anomalies changes radically. The transitional period is a time of both an accelerated search in practice and in theory for new mechanisms, and an increase in the possibility of a rollback in development: as an element of progress or as a generalizing trend of transformations. At the same time, cyclical and translational, wave-like and irreversible processes, trends of progress and regress. The inversion phenomena of non-classical transformations require a more complete use in the process of social regulation of naturally matured socio-economic forms, when the strategy of the “progressors” “to do good by force” only exacerbates contradictions, leads to overspending of resource bases and causes rejection. The final success of the transition significantly depends on the quality of organizational and managerial relations. For example, an effective solution may be to single out the core of development in everyday reality, to cultivate and build it up through two-loop control. On the one hand, teachings of a conservative, liberal and social democratic orientation offer their own paths for transformation; on the other hand, national sovereignties or transnational corporations / associations become the core of the search. Optimizing the course of change involves taking into account changes not only at the micro, but also at the macro level [1-5]. Thus, the feature that determines the range of both emerging strategic transformations and the impact on them is the transition: from the economy of simple labor to the economy of unique creativity; from exogenous quantitative growth to endogenous qualitative development; from the dominant of the material to the spiritual, moral and intellectual; from formational to non-formational; from exchange based on the comparison of goods to exchange based on the comparison of abilities; from conceptual openness to recognition of the right to intrinsic value and isolation of cultural and civilizational worlds; from cosmopolitanism / nationalism to regionalism and strategic partnership; from the unity of globalism patterns to post-global diversity [6-17].